Speech development in elementary school students and ways to develop vocabulary - Musaeva, N.S.; Khamidova, M.P. (International Journal of Psychosocial Rehabilitation, 2020)
This article provides recommendations for the implementation of corrective work aimed at eliminating speech disorders, vocabulary development in mentally retarded children. Keywords–, ,